The Relationship Between Depression and Hypertension Incident in Pregnant Women - Dycka Widyasti Genatha (Universitas Airlangga, 2018)
Background: The prevalence of hypertension in pregnancy reaches 5-15% and is one of the three causes of maternal mortality and morbidity. Risk factors for hypertension include work stress, low social support, quality of life, and the degree of depression a person has. Purpose: This study aimed to determine the relationship between depression and the incidence of hypertension. Method: This type of research is observational analytic with cross sectional approach. The study sample was a number of pregnant women in the Kalijudan Health Center as many as 38 respondents. The sampling technique is simple random sampling. Primary data obtained from examination result of the blood pressure from the respondents while conducting an examination at the Maternal and Child Health Clinic and the results of interviews using the Edinburgh Postnatal Depression Scale questionnaire (EPDS) to measure the degree of depression. The analysis used was univariate and bivariate analysis using Chi-square test. Results: The study showed that 21 out of 38 respondents experiencing depression (55.30%) and 12 respondents experiencing hypertension (31.60%). Hypertension in Kalijudan Community Health Center is more common in pregnant women with characteristics in the age group of early adulthood, second trimester of pregnancy, high education, income level is greater than provincial minimum wage (UMR), and experiencing depression. Conclusion: There is a relationship between depression and the incidence of hypertension in pregnant women at Kalijudan Health Center (p = 0.01). Prevalence Ratio (PR) was obtained at 4.05 which means the pregnant women who were depressed at Kalijudan Health Center had a risk of 4.05 times greater to have hypertension compared to pregnant women who did not experience depression